2022
DOI: 10.1007/s11356-021-18087-w
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution and tourism growth relationship: exploring regional dynamics in five European countries through an EKC model

Abstract: The present study intends to explore the relationship between tourism growth and air pollution at a regional level for five important tourism European destinations: France, Spain, Greece, Portugal, and Italy. Most of the studies found in the literature examine this relationship on a national scale and focus only on the CO 2 pollutant, which is a greenhouse gas but not a critical pollutant in terms of air quality and human exposure. This research focuses on a regional basis (NUTS 2 classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 78 publications
0
11
0
Order By: Relevance
“…In the 2000s, an increasing volume of environmental protection regulations appeared in the tourism policy agenda [33] and the link between tourism expansion and the EKC acquired prominence. While much research on tourism-induced EKC has used this theory as a proxy for CO 2 emissions from environmental deterioration [11,34], few studies have integrated two or three theories to investigate the link between international tourist arrivals and CO 2 emissions [1,7]. Since international tourism depends on many internal and external factors, such as safety and security [35], accessibility, policy stability, freedom of mobility, pull and push factors, etc.…”
Section: Literature Review 21 Theoretical Settingmentioning
confidence: 99%
“…In the 2000s, an increasing volume of environmental protection regulations appeared in the tourism policy agenda [33] and the link between tourism expansion and the EKC acquired prominence. While much research on tourism-induced EKC has used this theory as a proxy for CO 2 emissions from environmental deterioration [11,34], few studies have integrated two or three theories to investigate the link between international tourist arrivals and CO 2 emissions [1,7]. Since international tourism depends on many internal and external factors, such as safety and security [35], accessibility, policy stability, freedom of mobility, pull and push factors, etc.…”
Section: Literature Review 21 Theoretical Settingmentioning
confidence: 99%
“…Moreover, studies from Allard et al (2018) for a panel of 74 countries, Benedek and Ferto † (2020) for the countries where forest cover increased and Gyamfi et al (2021), for E7 countries, have confirmed N-shaped EKC. Studies from Ganda (2019) for South Africa, Pata and Caglar (2021) for China, Ciarlantini et al (2022) for five European countries and Massagony and Budiono (2023) have not validated the EKC. The stochastic impacts by regression on population affluence and technology (STIRPAT) framework also tests the impact of economic activities on environmental quality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yildırım et al (2021) tested the tourism-EKC hypothesis for 15 Mediterranean countries and found that tourist arrivals increased carbon emissions until a certain threshold was reached and then decreased carbon emissions above this level [ 38 ]. Ciarlantini et al (2022) explored the relationship between air pollution and tourism growth in five European countries and failed to validate the tourism-EKC hypothesis for any of the countries [ 27 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tian et al (2021) found that a 1% increase in tourism development leads to a 0.05% decrease in CO 2 emissions in the long run in G20 economies [10]. Ciarlantini et al (2022) found some differences in the impacts of international and local tourism on air pollution, that is, that international tourism negatively affects NO x , PM 10 , and PM 2.5 emissions, while local tourism increases their emissions [27].…”
Section: The Effect Of Tourism On Air Pollutionmentioning
confidence: 99%